Leaderships of opposition to Lula’s first rule: the case of PSDB (2012)
From the perspective of the analysis of political speeches and political identities, the aim of this article is to reach a general understanding of the strategies of three important leaders of the PSDB opposing Lula during different controversial moments in his first rule. Thus, we will analyze the discourses of Geraldo Alckmin, José Serra and Fernando Henrique Cardoso, considering them as representatives of the characteristics assumed by this space of party opposition during the period. Through this analysis, it will be possible to understand the ways in which these leaders appear as differentiated with respect to Lula’s first rule. We will characterize these ways as: a) differentiation by denounce of the contradictions, b) differentiation by denounce of the corruption and inefficiency and c) differentiation by hierarchical and intellectual disqualification. The analysis of these forms of differentiation will allow us to understand the difficulties that these party leaders are confronted with in their aim to produce a relationship between the differentiations of their political space of opposition and the production of an extended sociopolitical representation in the national level.